Desquamative Esophagitis Secondary to Mucous Membrane Pemphigoid in a Three-Year-Old Child: A Rare Case Report - Sainath Preetam; Dr Meenakshi Swain; Ramesh Srinivasan (The Indonesian Society of Pediatric Gastroenterology, Hepatology, and Nutrition, 2026)
Background: Esophagitis dissecans superficialis (EDS) is an uncommon disorder characterized by sloughing of the esophageal mucosa. Paediatric cases are infrequent and esophageal involvement due to mucous membrane pemphigoid (MMP) is exceptionally rare. We report a young child presenting with recurrent hematemesis secondary to EDS caused by MMP Case: A previously healthy three-year-old girl presented with hematemesis. Upper gastrointestinal endoscopy revealed severe desquamative esophagitis. Initial treatment with proton pump inhibitors resulted in temporary resolution, however symptoms recurred three months later. Careful examination identified intermittent blistering skin lesions. Skin biopsy and direct immunofluorescence demonstrating linear IgG deposition along the basement membrane zone confirmed MMP. Treatment with systemic corticosteroids and azathioprine resulted in sustained remission over 52 months of follow-up. Discussion: The absence of obvious mucocutaneous manifestations initially delayed diagnosis. Recurrent EDS should prompt evaluation for autoimmune blistering disorders. Multidisciplinary assessment and direct immunofluorescence were crucial for establishing the diagnosis and guiding treatment. Conclusion: Mucous membrane pemphigoid should be considered in children with recurrent desquamative esophagitis or unexplained hematemesis. Early diagnosis and immunosuppressive therapy may prevent long-term oesophageal complications and achieve durable remission.